Assessing the Impact of Boko Haram’s Terrorist Activities in the North East Region of Nigeria - Etor, Charity; Asekhauno, Anthony Afe (Journal of Contemporary International Relations and Diplomacy, 2024)
This paper examined the impact Boko Haram in Northeast with special reference to the Lake Chad Basin (LCB). It will focus on the growing climate of insecurity in the region owing to the emergence of terrorism across the country particularly in the Northeast geopolitical zone. The analytical foundations was built upon the meaning of security, insecurity, tensions in the Northeast making reference to (LCB), the impacts on socio-political and economic relations among the occupants of the region such as high rate of death, unemployment, poverty as well as malnutrition in the North East Nigeria. It will proceed to the causes and the sustaining factors driving the insecurity in the region, the difficulties and failure facing Nigerian government to eliminate the Boko-Haram. The work uses secondary sources of data collection such as journal articles, newspaper, magazine, internet materials, books and others. This paper applied social identity and structural functionalism theories to better explain and analyze factors that aided the terrorist group. The paper discovered that the reason for the continuous attack of the Northeast region by the Bokoharam sect includes religious indoctrination, existence of porous border etc. the paper recommend that government should provide adequate border security and that there should be a campaign for the de orientation of religious radicalism in the region.